Bioactive reagents used in mesotherapy for skin rejuvenation in vivo induce diverse physiological processes in human skin fibroblasts in vitro - a pilot study - Jäger, Claudia; Brenner, Christiane; Habicht, Jüri; Wallich, Reinhard (Experimental dermatology, 2012)
Abstract: The promise of mesotherapy is maintenance and/or recovery of a youthful skin with a firm, bright and moisturized texture. Currently applied medications employ microinjections of hyaluronic acid, vitamins, minerals and amino acids into the superficial layer of the skin. However, the molecular and cellular processes underlying mesotherapy are still elusive. Here we analysed the effect of five distinct medication formulas on pivotal parameters involved in skin ageing, that is collagen expression, cell proliferation and morphological changes using normal human skin fibroblast cultures in vitro. Whereas in the presence of hyaluronic acid, NCTF135® and NCTF135HA®, cell proliferation was comparable to control cultures; however, with higher expression of collagen type-1, matrix metalloproteinase-1 and tissue inhibitor of matrix metalloproteinase-1, addition of Soluvit® N and Meso-BK led to apoptosis and/or necrosis of human fibroblasts. The data indicate that bioactive reagents currently applied for skin rejuvenation elicit strikingly divergent physiological processes in human skin fibroblast in vitro.